Graphene cement additive, graphene-cement composite material and preparation method of graphene-cement composite material
By using pure water and surfactant liquid phase peeling method in graphene preparation, the brittleness and low toughness of cement-based composite materials are solved, and the efficient and low-cost preparation of graphene is achieved, which significantly improves the cement concrete Mechanical properties.
Patent Information
- Application Number
- CN202311008556.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-10
AI Technical Summary
Existing cement-based composite materials have brittleness and low toughness, which is difficult to meet the high requirements for material performance in the construction industry and large-scale projects. At the same time, during the graphene preparation process, the surface tension of graphene and water does not match, making it difficult to obtain high-quality Graphene.
Pure water is used as the release agent, and by adding bile salt anionic surfactant and nonionic surfactant, liquid phase peeling is performed using ultrasonic technology to prepare graphene cement additives that can be used as cement additives.
The efficient preparation of graphene is achieved, cost reduction and yield improvement, and graphene cement additives can significantly improve the mechanical properties of cement concrete and meet the needs of the construction industry.
Smart Images

Figure CN119461929A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of graphene preparation, and specifically relates to a method for preparing a liquid-phase exfoliated graphene cement additive and the graphene cement additive prepared thereby, and also relates to a method for preparing a graphene-cement composite material and the graphene-cement composite material prepared thereby. Background Art
[0002] The continuous development of the construction industry and large-scale projects has put forward more and higher requirements on the performance of cement-based composite materials. However, the brittleness and low toughness of cement-based composite materials can no longer meet the current development requirements of the construction industry and large-scale projects. At the same time, it has also limited the development and application of cement and its composite materials to a certain extent.
[0003] Graphene is a new type of two-dimensional structural material with a single-layer sheet structure consisting of six-membered rings formed by sp2 hybridized carbon atoms connected by covalent bonds (Electrochimica Acta, 2010, 56: 491-500). It has excellent mechanical properties and is the material with the highest hardness and strength known so far. As a new type of high-performance nanomaterial, graphene has unique mechanical properties and nano-size effects, and has become a research hotspot in the field of materials science. Previous studies have shown that the addition of optimized graphene to cement-based materials exhibits excellent reinforcement effects and improves the comprehensive performance of cement-based materials.
[0004] Among the many graphene preparation methods currently available, the liquid phase exfoliation method is relatively simple to operate, low in cost, and has a high product quality. It is currently the only preparation method that can achieve large-scale preparation of graphene while maintaining the complete morphology and performance of graphene. This method is to disperse graphite in an appropriate solvent, then apply a strong shear force to overcome the van der Waals force between graphite layers and exfoliate to obtain graphene. The exfoliated graphene product obtained by this method can exist in the form of a dispersion or slurry, which is very convenient to transport and reuse.
[0005] In the process of preparing graphene, organic solvents are the first substances used as stripping media (Advanced functional materials, 2009, 19: 3680-95), but organic solvents have some disadvantages such as high toxicity, high price, poor biocompatibility and difficulty in separation when used as stripping media. Therefore, water, as a colorless, tasteless, non-toxic and harmless liquid with good reproducibility, is considered to be the most environmentally friendly solvent. Using water to strip graphene is the most important means to achieve large-scale production and has good application prospects in industrialization. However, due to the mismatch between the surface tension of graphene and water, the graphite raw material is subjected to ultrasonic or shear stripping in pure water, which often can only obtain micron-level graphite fragments, making it difficult to obtain graphene. Therefore, it is found that adding an appropriate amount of surfactant to water to reduce the surface tension of water is an effective solution to the problem of surface tension mismatch. At the same time, different surfactants have different effects on exfoliating graphene due to their different structural properties. According to the different ionization states of surfactants in water, surfactants can be divided into two categories: ionic and non-ionic. Anionic surfactants are more commonly used because of their low price, but at the same time, non-ionic surfactants are better than ionic surfactants in dispersing / exfoliating original graphite in water under ultrasound assistance (2011, carbon, 49: 1653-62). Therefore, the dispersion of graphene in surfactant / water system may be the most promising, which can not only avoid the use of toxic solvents, but also reduce the agglomeration of graphene sheets.
[0006] In view of this, how to further improve the exfoliation effect of graphene, reduce costs to make it easy to mass-produce without solvent residue, and then mix it into cement to improve the mechanical strength of cement concrete is the current research focus. Summary of the invention
[0007] In order to solve the above deficiencies in the prior art, the present invention utilizes green and pollution-free pure water as a stripping agent, adds a small amount of surfactant, and adopts an economical ultrasonic process for liquid phase stripping to obtain graphene that can be used as a cement additive, thereby reducing costs and increasing production. Graphene is then further blended into cement to achieve the purpose of improving the mechanical properties of cement concrete.
[0008] According to a first aspect of the present invention, a method for preparing a liquid phase exfoliated graphene cement additive is provided, comprising the following steps:
[0009] Step S1: preparing a stripping agent solution using pure water, bile salt anionic surfactant and nonionic surfactant, adding graphite raw material to the prepared stripping agent solution, and stirring and mixing them thoroughly to obtain a graphite pre-stripping dispersion;
[0010] Step S2: The graphite pre-exfoliation dispersion obtained in step S1 is subjected to auxiliary exfoliation dispersion by water bath ultrasound to obtain a graphene mixed dispersion system:
[0011] Step S3: centrifuge the graphene mixed dispersion system obtained in step S2, take the upper layer solution for dialysis, remove the unpeeled particles or thick graphite sheets, and obtain the graphene cement additive.
[0012] According to some embodiments of the present invention, in step S1, the bile salt anionic surfactant is one of sodium cholate (SC), sodium deoxycholate (SDC), sodium taurodeoxycholate (STC), and sodium deoxycholate (NaDC).
[0013] According to some embodiments of the present invention, in step S1, the nonionic surfactant is one of polyvinyl pyrrolidone (PVP), fatty alcohol polyoxyethylene ether (AEO), amine oxide and alkyl polyglycoside (APG), and Tween 80.
[0014] According to some embodiments of the present invention, in step S1, the ratio of the bile salt anionic surfactant to the nonionic surfactant is 1:1 mg / mL.
[0015] According to some embodiments of the present invention, in the stripper solution, the concentration of the bile salt anionic surfactant is 1-10 wt %, and the concentration of the nonionic surfactant is 1-10 wt %.
[0016] According to some embodiments of the present invention, in step S1, the graphite raw material is one or more of graphite powder, natural graphite, natural flake graphite, spherical graphite, expandable graphite, oxidized graphite powder, and oriented pyrolytic graphite.
[0017] According to some embodiments of the present invention, in step S1, the concentration of the graphite raw material in the prepared stripping agent solution is 0.1-20 wt %.
[0018] According to some embodiments of the present invention, in step S1, the stirring is magnetic stirring, the rotation speed is 500-2000 rpm, and the stirring time is 0.5-5 hours.
[0019] According to some embodiments of the present invention, in step S2, stirring is performed for 5 minutes every 30 minutes during the ultrasonic process.
[0020] According to some embodiments of the present invention, in step S2, the ultrasonic frequency range is 20-70 kHz, and the ultrasonic time is 0.5-12 hours.
[0021] According to some embodiments of the present invention, in step S3, the centrifugal speed is 5000-20000 rpm, and the centrifugal time is 5-30 minutes.
[0022] According to a second aspect of the present invention, a graphene cement additive is provided. The graphene cement additive is prepared by the method according to the first aspect of the present invention.
[0023] According to a third aspect of the present invention, there is provided a method for preparing a graphene-cement composite material, comprising the following steps:
[0024] Step S1: preparing a stripping agent solution using pure water, bile salt anionic surfactant and nonionic surfactant, adding graphite raw material to the prepared stripping agent solution, and stirring and mixing them thoroughly to obtain a graphite pre-stripping dispersion;
[0025] Step S2: The graphite pre-exfoliation dispersion obtained in step S1 is subjected to auxiliary exfoliation dispersion by water bath ultrasound to obtain a graphene mixed dispersion system:
[0026] Step S3: centrifuging the graphene mixed dispersion system obtained in step S2, taking the upper layer solution for dialysis, removing the unpeeled particles or thick graphite sheets, and obtaining a graphene cement additive;
[0027] Step S4: adding the graphene cement additive obtained in step S3 to cement, mixing, and obtaining a graphene-cement composite material.
[0028] According to some embodiments of the present invention, in step S4, the addition ratio of the graphene cement additive is 0.1-30wt%.
[0029] According to a fourth aspect of the present invention, a graphene-cement composite material is provided. The graphene-cement composite material is prepared by the method according to the third aspect of the present invention.
[0030] Due to the adoption of the above technical solution, the present invention has at least one of the following beneficial effects compared with the prior art:
[0031] 1. The present invention adopts a liquid phase exfoliation method to prepare graphene. This method is not only simple in process and easy to operate, but can also effectively separate graphite sheets and obtain a large amount of graphene in a short time. The prepared graphene is a single layer or a few layers, has good electrical / thermal properties, and excellent comprehensive properties, and is expected to realize the industrial preparation of graphene.
[0032] 2. The present invention uses water as a stripping agent. Water is a colorless, odorless, non-toxic, harmless liquid with good renewable ability. It is considered to be the most environmentally friendly solvent. Using water to strip graphene is the most important means to achieve large-scale production and has good application prospects in industrialization.
[0033] 3. The present invention adopts bile salt anionic surfactant and nonionic surfactant to reduce the high surface tension of water. Anionic surfactant is cheap and has good dispersibility, and nonionic surfactant has good solubility. The synergistic effect of the two can achieve good dispersion of graphene. In addition, the residual surfactant can be directly added to the cement material as an additive. The residual surfactant can be grafted on the surface of graphene, which can further enhance the hydrophilicity of graphene, thereby ensuring the performance of graphene in the cement matrix, so that graphene can form a better mixed system with cement. Therefore, there is no need to remove the surfactant step.
[0034] 4. The exfoliated graphene product obtained by the present invention can exist in the form of a dispersion or slurry, which is very convenient to transport and reuse. It can be directly used as a cement additive and added and mixed when preparing cement mortar. It has a good fusion effect with cement and can reduce the agglomeration of graphene.
[0035] 5. The stripping agent and surfactant used in the present invention are cheap and easily available. The liquid phase stripping method used is simple to operate, efficient, green and environmentally friendly, and can directly obtain graphene cement additives without secondary processing. Adding it to cement not only reduces the cost of directly adding graphene, but also promotes the fusion of graphene and cement. At the same time, according to GB / T 17671-2020 "Test Method for Strength of Cement Mortar (ISO Method)", cement mortars of different ages are measured. The compressive strength of the cement mortar prepared by this method is also greatly improved, which improves the mechanical properties of cement and meets the needs of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A flow chart of the method for preparing the liquid phase exfoliated graphene cement additive provided by the present invention;
[0037] Figure 2 A flow chart of a method for preparing a graphene-cement composite material provided by the present invention;
[0038] Figure 3 This is a scanning electron microscope photo of the graphene cement additive prepared in Example 1;
[0039] Figure 4 This is a transmission electron microscope photo of the graphene cement additive prepared in Example 1;
[0040] Figure 5 This is an X-ray powder diffraction spectrum of the graphene cement additive prepared in Example 1;
[0041] Figure 6 This is a comparison chart of the compressive strength of the graphene-cement composite material prepared in Example 4 and the corresponding comparative example;
[0042] Figure 7 This is a comparison chart of the compressive strength of the graphene-cement composite material prepared in Example 5 and the corresponding comparative example;
[0043] Figure 8 This is a comparison chart of the compressive strength of the graphene-cement composite material prepared in Example 6 and the corresponding comparative example. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] According to a first aspect of the present invention, a method for preparing a liquid phase exfoliated graphene cement additive is provided. Figure 1 As shown, the preparation method of liquid-phase exfoliated graphene cement additive comprises the following steps: step S1: preparing an exfoliator solution using pure water, bile salt anionic surfactant and nonionic surfactant, adding graphite raw material to the prepared exfoliator solution, stirring and mixing thoroughly to obtain a graphite pre-exfoliation dispersion; step S2: subjecting the graphite pre-exfoliation dispersion obtained in step S1 to auxiliary exfoliation dispersion by water bath ultrasound to obtain a graphene mixed dispersion system; step S3: centrifuging the graphene mixed dispersion system obtained in step S2, taking the upper solution for dialysis, removing unexfoliated particles or thick graphite sheets, and obtaining a graphene cement additive.
[0046] In some embodiments, in step S1, the bile salt anionic surfactant may be one of sodium cholate (SC), sodium deoxycholate (SDC), sodium taurodeoxycholate (STC), sodium deoxycholate (NaDC), and the nonionic surfactant may be one of polyvinyl pyrrolidone (PVP), fatty alcohol polyoxyethylene ether (AEO), amine oxide and alkyl polyglycoside (APG), Tween 80. In some embodiments, preferably, in step S1, the ratio of the bile salt anionic surfactant to the nonionic surfactant may be 1:1 mg / mL, preferably, in the stripper solution, the concentration of the bile salt anionic surfactant may be 1-10wt%, and the concentration of the nonionic surfactant may be 1-10wt%. Herein, the concentration of the bile salt anionic surfactant refers to the percentage of the mass of the bile salt anionic surfactant to the total mass of the stripper solution, and the concentration of the nonionic surfactant refers to the percentage of the mass of the nonionic surfactant to the total mass of the stripper solution. Specifically, in the stripping agent solution, the concentration of bile salt anionic surfactant and the concentration of nonionic surfactant can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, or any value therebetween.
[0047] In some embodiments, in step S1, the graphite raw material may be one or more of graphite powder, natural graphite, natural flake graphite, spherical graphite, expandable graphite, oxidized graphite powder, and oriented pyrolytic graphite.
[0048] In some embodiments, preferably, in step S1, the concentration of the graphite raw material in the prepared stripper solution may be 0.1-20wt%. Specifically, the concentration of the graphite raw material in the prepared stripper solution may be 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt% or any value therebetween.
[0049] In some embodiments, preferably, in step S1, the stirring may be magnetic stirring, the rotation speed may be 500-2000 rpm, and the stirring time may be 0.5-5 hours. Specifically, the rotation speed may be 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm or any value therebetween, and the stirring time may be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h or any value therebetween.
[0050] In some embodiments, preferably, in step S2, stirring for 5 minutes every 30 minutes during the ultrasonic process helps to eliminate the adhesion of graphite on the agitator, so that the graphite is better dispersed in the solution, and then the homogeneity of graphite exfoliation is achieved. In some embodiments, preferably, in step S2, the ultrasonic frequency range is 20-70kHz, and the ultrasonic time is 0.5-12 hours. Specifically, the ultrasonic frequency range can be 20kHz, 30kHz, 40kHz, 50kHz, 60kHz, 70kHz or any value therebetween, and the ultrasonic time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value therebetween.
[0051] In some embodiments, preferably, in step S3, the centrifugal speed is 5000-20000 rpm, and the centrifugal time is 5-30 minutes. Specifically, the centrifugal speed can be 5000 rpm, 10000 rpm, 15000 rpm, 20000 rpm or any value therebetween, and the centrifugal time can be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes or any value therebetween.
[0052] According to a second aspect of the present invention, a graphene cement additive is provided. The graphene cement additive is prepared by the method according to the first aspect of the present invention.
[0053] According to a third aspect of the present invention, a method for preparing a graphene-cement composite material is provided. Figure 2As shown, the preparation method of graphene-cement composite material comprises the following steps: step S1: prepare stripping agent solution by using pure water, bile salt anionic surfactant and nonionic surfactant, add graphite raw material to the prepared stripping agent solution, stir and mix thoroughly to obtain graphite pre-stripping dispersion; step S2: the graphite pre-stripping dispersion obtained in step S1 is subjected to water bath ultrasound to assist in stripping and dispersion to obtain a graphene mixed dispersion system: step S3: centrifuge the graphene mixed dispersion system obtained in step S2, take the upper solution for dialysis, remove the unstripped particles or thick graphite sheets, and obtain a graphene cement additive; step S4: add the graphene cement additive obtained in step S3 to cement, mix, and obtain a graphene-cement composite material. Steps S1-S3 here are the same as steps S1-S3 described in the first aspect of the present invention, and will not be repeated here.
[0054] In some embodiments, preferably, in step S4, the addition ratio of the graphene cement additive is 0.1-30wt%. Specifically, the addition ratio of the graphene cement additive can be 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or any value therebetween.
[0055] According to a fourth aspect of the present invention, there is provided a graphene-cement composite material, which is prepared by the method according to the third aspect of the present invention.
[0056] The present invention is described in detail below through specific examples. In the following examples, unless otherwise specified, all the raw materials used are commercially available.
[0057] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0058] The present invention will be described in detail below with reference to specific embodiments.
[0059] Preparation Example of Graphene Cement Additive
[0060] Example 1
[0061] A method for preparing a liquid-phase exfoliated graphene cement additive comprises the following specific steps:
[0062] 1) A mixed aqueous solution of sodium cholate (SC) and polyvinyl pyrrolidone (PVP) at a concentration of 1 wt% is prepared in pure water, 10 g of graphite powder is dispersed in 90 g of the solution to obtain a 10 wt% graphite solution, the solution is stirred for 2 h under magnetic stirring at a speed of 1000 rpm to fully stir and mix, and the obtained graphite pre-exfoliation dispersion is placed in a sealed container.
[0063] 2) The graphite pre-exfoliation dispersion was subjected to ultrasonic treatment at room temperature for 6 hours for auxiliary exfoliation dispersion, the ultrasonic frequency was set to 60 kHz, and the mixture was stirred for 5 minutes every 30 minutes during the ultrasonic process to obtain a graphene mixed dispersion system.
[0064] 3) Using a centrifuge, the graphene mixed dispersion system is centrifuged, the selected centrifuge speed is 18000 rpm, the centrifugation time is 10 minutes, the upper layer solution is dialyzed to remove the unpeeled particles or thick graphite sheets, and the graphene cement additive is obtained.
[0065] Example 2
[0066] A method for preparing a liquid-phase exfoliated graphene cement additive comprises the following specific steps:
[0067] 1) A mixed aqueous solution of sodium cholate (SC) and polyvinyl pyrrolidone (PVP) at a concentration of 10 wt% is prepared in pure water, 1 g of graphite powder is dispersed in 999 g of the solution to obtain a 0.1 wt% graphite solution, the solution is stirred for 2 h under magnetic stirring at a speed of 1000 rpm to fully stir and mix, and the obtained graphite pre-exfoliation dispersion is placed in a sealed container.
[0068] 2) The graphite pre-exfoliation dispersion was subjected to ultrasonic treatment at room temperature for 6 hours for auxiliary exfoliation dispersion, the ultrasonic frequency was set to 60 kHz, and the mixture was stirred for 5 minutes every 30 minutes during the ultrasonic process to obtain a graphene mixed dispersion system.
[0069] 3) Using a centrifuge, the graphene mixed dispersion system is centrifuged, the selected centrifuge speed is 18000 rpm, the centrifugation time is 10 minutes, the upper layer solution is dialyzed to remove the unpeeled particles or thick graphite sheets, and the graphene cement additive is obtained.
[0070] Example 3
[0071] A method for preparing a liquid-phase exfoliated graphene cement additive comprises the following specific steps:
[0072] 1) A mixed aqueous solution of sodium deoxycholate (SDC) and fatty alcohol polyoxyethylene ether (AEO) with a concentration of 5 wt% is prepared in pure water, 1 g of graphite powder is dispersed in 99 g of the solution to obtain a 1 wt% graphite solution, the solution is stirred for 3 h under magnetic stirring at a speed of 1000 rpm to fully stir and mix, and the obtained graphite pre-exfoliation dispersion is placed in a sealed container.
[0073] 2) The graphite pre-exfoliation dispersion was subjected to ultrasonic treatment at room temperature for 8 hours for auxiliary exfoliation dispersion, the ultrasonic frequency was set to 60 kHz, and stirring was continued for 5 minutes every 30 minutes during the ultrasonic process to obtain a graphene mixed dispersion system.
[0074] 3) Using a centrifuge, the graphene mixed dispersion system is centrifuged, the selected centrifuge speed is 18000 rpm, the centrifugation time is 20 minutes, the upper layer solution is dialyzed to remove the unpeeled particles or thick graphite sheets, and the graphene cement additive is obtained.
[0075] Example 4
[0076] A method for preparing a liquid-phase exfoliated graphene cement additive comprises the following specific steps:
[0077] 1) A mixed aqueous solution of sodium deoxycholate (SDC) and fatty alcohol polyoxyethylene ether (AEO) with a concentration of 5 wt% is prepared in pure water, 20 g of graphite powder is dispersed in 80 g of the solution to obtain a 20 wt% graphite solution, the solution is stirred under magnetic stirring for 3 h at a speed of 1000 rpm to fully stir and mix, and the obtained graphite pre-exfoliation dispersion is placed in a closed container.
[0078] 2) The graphite pre-exfoliation dispersion was subjected to ultrasonic treatment at room temperature for 8 hours for auxiliary exfoliation dispersion, the ultrasonic frequency was set to 60 kHz, and stirring was continued for 5 minutes every 30 minutes during the ultrasonic process to obtain a graphene mixed dispersion system.
[0079] 3) Using a centrifuge, the graphene mixed dispersion system is centrifuged, the selected centrifuge speed is 18000 rpm, the centrifugation time is 20 minutes, the upper layer solution is dialyzed to remove the unpeeled particles or thick graphite sheets, and the graphene cement additive is obtained.
[0080] Preparation Example of Graphene-Cement Composite Material
[0081] Example 5
[0082] The graphene cement additive prepared in Example 1 was added to cement at a ratio of 2 wt %, and a graphene-cement composite material was obtained by mixing.
[0083] Example 6
[0084] The graphene cement additive prepared in Example 2 was added to cement at a ratio of 1.5 wt % to obtain a graphene-cement composite material.
[0085] Example 7
[0086] The graphene cement additive prepared in Example 3 was added to cement at a ratio of 2.5 wt %, and a graphene-cement composite material was obtained by mixing.
[0087] Example 8
[0088] The graphene cement additive prepared in Example 1 was added to cement at a ratio of 0.1 wt %, and a graphene-cement composite material was obtained by mixing.
[0089] Example 9
[0090] The graphene cement additive prepared in Example 1 was added to cement at a ratio of 15 wt % to obtain a graphene-cement composite material.
[0091] Example 10
[0092] The graphene cement additive prepared in Example 1 was added to cement at a ratio of 30 wt %, and a graphene-cement composite material was obtained by mixing.
[0093] Testing and characterization of graphene cement additives
[0094] The graphene cement additive prepared in the above embodiment was tested and characterized, and the specific method is as follows: the microscopic morphology of the prepared graphene cement additive was characterized using a scanning electron microscope and a transmission electron microscope. The crystal structure of the material was determined using an X-ray powder diffractometer.
[0095] Figure 3 This is a scanning electron microscope photograph of the graphene cement additive prepared in Example 1. The results show that the graphene cement additive has a relatively loose structure and there is no obvious stacking between the layers.
[0096] Figure 4 This is a transmission electron microscope photograph of the graphene cement additive prepared in Example 1. The results show that the graphene cement additive has a thin layer structure with less than 10 layers.
[0097] Figure 5 This is the X-ray powder diffraction spectrum of the graphene cement additive prepared in Example 1. The results show that the 002 peak intensity of the graphene cement additive is low and relatively broad, which also confirms the thin layer structure of the graphene cement additive.
[0098] Performance characterization of graphene-cement composites
[0099] After the prepared graphene-cement composite mortar is loaded into the mold, a 40mm×40mm×160mm specimen is prepared, placed on a vibration table for 5 minutes, and then placed in a curing box at room temperature of 20°C and humidity greater than 95% for curing. The compressive strength is then measured and cured to the specified age under standard curing conditions.
[0100] At the same time, a cement specimen without graphene additives was prepared as a blank group for control. Cement and mixing water were mechanically compounded, and cement mortar was prepared according to standard requirements to prepare a 40mm×40mm×160mm cement mortar specimen, which was placed on a vibration table for 5 minutes and then placed in a curing box at room temperature of 20°C and humidity greater than 95% for curing, and then the compressive strength was measured. It was cured under standard curing conditions to the specified age, and then the compressive strength was measured as a control group.
[0101] The strength of cement mortar products cured for 3 days, 7 days and 28 days was measured according to GB / T 17671-1999 “Test method for strength of cement mortar (ISO method)”.
[0102] Figure 6 The experimental results of the graphene-cement composite material prepared in Example 5 and the blank group are as follows: Figure 6 As shown, after curing for 3 days, 7 days and 28 days, the compressive strength of the graphene-cement composite material prepared in Example 5 was 25.5, 34.6 and 54.9 MPa, respectively, which was increased by 21.4%, 23.6% and 27.7% respectively compared with the strength of the cement specimen without adding graphene additives. Figure 7 The experimental results of the graphene-cement composite material prepared in Example 6 and the blank group are as follows: Figure 7 As shown, after curing for 3 days, 7 days and 28 days, the compressive strength of the graphene-cement composite material prepared in Example 6 was 25.6, 34.5 and 54.6 MPa, respectively, which was increased by 21.9%, 23.2% and 26.9% respectively compared with the strength of the cement specimen without adding graphene additives. Figure 8 The experimental results of the graphene-cement composite material prepared in Example 7 and the blank group are as follows: Figure 8As shown, the compressive strength of the graphene-cement composite material prepared in Example 7 after curing for 3 days, 7 days and 28 days was 26.5, 34.8 and 55.2 MPa, respectively, which was 26.2%, 24.3% and 28.4% higher than the strength of the cement specimen without adding graphene additives. In addition, the experimental results of the graphene-cement composite materials prepared in Examples 8-10 and the blank group also showed that the compressive strength of the graphene-cement composite material after curing for 3 days, 7 days and 28 days was increased by more than 20% compared with the strength of the cement specimen without adding graphene additives. It can be seen that after the graphene cement additive prepared by the present invention is mixed with cement as an additive, the compressive strength of cement is greatly improved.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention, including the combination of various technical features in any other appropriate manner, these simple variations and combinations should also be regarded as the contents disclosed by the present invention and should be included in the protection scope of the present invention.
Claims
1. A method for preparing a liquid phase exfoliated graphene cement additive, characterized in that: The following steps are involved: Step S1: preparing a stripping agent solution using pure water, bile salt anionic surfactant and nonionic surfactant, adding graphite raw material to the prepared stripping agent solution, and stirring and mixing them thoroughly to obtain a graphite pre-stripping dispersion; Step S2: The graphite pre-exfoliation dispersion obtained in step S1 is subjected to auxiliary exfoliation dispersion by water bath ultrasound to obtain a graphene mixed dispersion system: Step S3: centrifuge the graphene mixed dispersion system obtained in step S2, take the upper solution for dialysis, remove the unpeeled particles or graphite sheets, and obtain the graphene cement additive.
2. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the bile salt anionic surfactant is one of sodium cholate (SC), sodium deoxycholate (SDC), sodium taurodeoxycholate (STC), and sodium deoxycholate (NaDC).
3. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the nonionic surfactant is one of polyvinyl pyrrolidone (PVP), fatty alcohol polyoxyethylene ether (AEO), amine oxide, alkyl polyglycoside (APG), and Tween 80.
4. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the ratio of the bile salt anionic surfactant to the nonionic surfactant is 1:1 mg / mL.
5. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 4, characterized in that: In the stripping agent solution, the concentration of the bile salt anionic surfactant is 1-10 wt %, and the concentration of the nonionic surfactant is 1-10 wt %.
6. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the graphite raw material is one or more of graphite powder, natural graphite, natural flake graphite, spherical graphite, expandable graphite, oxidized graphite powder, and oriented pyrolytic graphite.
7. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the concentration of the graphite raw material in the prepared stripping agent solution is 0.1-20 wt %.
8. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S1, the stirring is magnetic stirring, the rotation speed is 500-2000 rpm, and the stirring time is 0.5-5 hours.
9. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S2, stirring was performed for 5 min every 30 min during the ultrasonic process.
10. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S2, the ultrasonic frequency range is 20-70 kHz, and the ultrasonic time is 0.5-12 hours.
11. The method for preparing the liquid phase exfoliated graphene cement additive according to claim 1, characterized in that: In step S3, the centrifugal speed is 5000-20000 rpm, and the centrifugal time is 5-30 minutes.
12. A graphene cement additive, characterized in that: The graphene cement additive is prepared by the method according to any one of claims 1 to 11.
13. A method for preparing a graphene-cement composite material, characterized in that: The following steps are involved: Step S1: preparing a stripping agent solution using pure water, bile salt anionic surfactant and nonionic surfactant, adding graphite raw material to the prepared stripping agent solution, and stirring and mixing them thoroughly to obtain a graphite pre-stripping dispersion; Step S2: The graphite pre-exfoliation dispersion obtained in step S1 is subjected to auxiliary exfoliation dispersion by water bath ultrasound to obtain a graphene mixed dispersion system: Step S3: centrifuging the graphene mixed dispersion system obtained in step S2, taking the upper layer solution for dialysis, removing the unpeeled particles or graphite sheets, and obtaining a graphene cement additive; Step S4: adding the graphene cement additive obtained in step S3 to cement, mixing, and obtaining a graphene-cement composite material.
14. The method for preparing the graphene-cement composite material according to claim 13, characterized in that: In step S4, the addition ratio of the graphene cement additive is 0.1-30wt%.
15. A graphene-cement composite material, characterized in that: The graphene-cement composite material is prepared by the method according to any one of claims 13-14.
Citation Information
Patent Citations
Graphene modified cement-based composite material and preparation method thereof
CN109553366A
Preparation method of graphene composite material and graphene composite material
CN114014308A
Single-layer graphene dispersion liquid and preparation method therefor
WO2016101208A1
Cited By
Grouting method based on graphene cement-based material in deep underground space
CN121952602A